Design and Implementation in Frontend Development of the PLN UP3 Yogyakarta SIBER Project with Tailwind and Bootstrap - Annisa Dinda Septina; Erika Ramadhani (Journal of Social Science, 2024)
In the Society 5.0 era which is characterized by mobility high and integration technology in everyday life, PLN UP3 Yogyakarta experienced operational obstacles, especially related to manual data processing and static websites. To overcome these challenges, a Joint Information System (SIBER) was developed as an application web- based which allows real-time data access for all employees. In SIBER development, the Scrum method is used for possible project management clear planning and flexibility in sprint iterations. In addition, the implementation of the Tailwind CSS framework and Bootstrap in the development of the SIBER user interface ensures a responsive and attractive appearance, with Tailwind providing detailed design flexibility and Bootstrap providing UI components that are tested and easy to use.